Tinjauan Yuridis Kedudukan dan Pelaksanaan Amicus Curiae dalam Sistem Pembuktian Peradilan Pidana: Studi Kasus Putusan Pengadilan Tinggi Medan Nomor 1495/PID.SUS/2020/PT MDN - Erissa Maydina Ciendy; Hervina Puspitosari (Jurnal Hukum Lex Generalis, 2025)
Amicus Curiae, commonly found in common law systems, is increasingly appearing in Indonesian courts as a third party offering legal opinions. This study aims to analyze the role of Amicus Curiae in proving criminal acts, particularly in case decision number 1495/PID.SUS/2020/PT MDN. The research method used is normative, with a doctrinal approach and case study. The findings indicate that, although there are no specific regulations governing the position of Amicus Curiae in Indonesian courts, their opinions can influence the judge’s decision in the case.